HUBUNGAN KARAKTERISTIK PASIEN DIABETES MELITUS DAN TINGKAT KEPATUHAN MINUM OBAT DI RSUD EMBUNG FATIMAH KOTA BATAM - Suci Fitriani Sammulia; Trie Yuni Elfasyari; M. Renaldy Pratama (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2020)
Based on data from the World Health Organization (WHO), the death rate from diabetes will increase 2/3 times between 2008 and 2030. Non-compliance in carrying out its treatment can result in low blood sugar control and can cause complications. The purpose of this study was to determine the relationship between the characteristics of diabetes mellitus patients and the level of adherence to take medication at Embung Fatimah District Hospital in Batam. The design of this study was an observational study using a quantitative descriptive method using a cross sectional design performed on patients with Diabetes mellitus in embung Fatimah Regional Hospital Batam in January to March 2019. The instrument used in this study was the medication compliance questionnaire using MMAS-8 (Morisky Medication Adherence Scale) that has been validated. Data analysis using chi square statistics. Based on the results of the level of adherence of the questionnaire answers to 96 patients, namely, patients with low adherence as many as 20 people (20.8%), moderate adherence as many as 45 people (46.9%) and high adherence as many as 31 people (32.3%). The relationship of the level of adherence which includes age, sex, length of suffering, and concomitant diseases has a p value (0.753; 0.882; 0.908; and 0.952) which shows no significant relationship. While the relationship of the level of compliance with the level of education showed a significant relationship with the value of p = 0.001.